A dynamic social systems model for considering structural factors in HIV prevention and detection. - Latkin, Carl; Weeks, Margaret R; Glasman, Laura; Galletly, Carol; Albarracin, Dolores (AIDS and behavior, 2010)
We present a model for HIV-related behaviors that emphasizes the dynamic and social nature of the structural factors that influence HIV prevention and detection. Key structural dimensions of the model include resources, science and technology, formal social control, informal social influences and control, social interconnectedness, and settings. These six dimensions can be conceptualized on macro, meso, and micro levels. Given the inherent complexity of structural factors and their interrelatedness, HIV prevention interventions may focus on different levels and dimensions. We employ a systems perspective to describe the interconnected and dynamic processes of change among social systems and their components. The topics of HIV testing and safer injection facilities (SIFs) are analyzed using this structural framework. Finally, we discuss methodological issues in the development and evaluation of structural interventions for HIV prevention and detection.
Keywords: HIV Infections; Humans; Interpersonal Relations; Models, Theoretical; Risk-Taking; Sexual Behavior; Social Control, Informal; Social Environment; Social Support; Systems Theory